2018
DOI: 10.5152/tud.2018.19677
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-invasive bladder and urethral cancer recurrence after surgical management of upper tract urothelial carcinoma: A review of 305 patients

Abstract: Objective: Bladder cancer recurrence after management of upper tract urothelial carcinoma (UTUC) is a common disease. Although the incidence and risk factors for the development of noninvasive bladder tumor have been reported in many series, rare studies have reported on muscle invasive bladder cancer (MIBC) and its urethral recurrence. We aimed to report the incidence, risk factors and survival rate for the development of MIBC and urethral tumors after surgical management of UTUC. Material and methods:We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We found that compared with RPT, UT was significantly correlated with inferior BRFS. In previous studies, the role of tumor location in bladder recurrence was not consistent; some found UT had a lower BRFS rate than RPT [21][22][23], but some concluded there was no difference between RPT and UT [24][25][26]. As mentioned, the actual impact of tumor location on prognosis can be revealed by excluding multifocal cases.…”
Section: Discussionmentioning
confidence: 93%
“…We found that compared with RPT, UT was significantly correlated with inferior BRFS. In previous studies, the role of tumor location in bladder recurrence was not consistent; some found UT had a lower BRFS rate than RPT [21][22][23], but some concluded there was no difference between RPT and UT [24][25][26]. As mentioned, the actual impact of tumor location on prognosis can be revealed by excluding multifocal cases.…”
Section: Discussionmentioning
confidence: 93%
“…The effective rates were higher than those of patients who underwent surgery alone reported in the literature [ 23 , 24 ] and similar to those of postoperative radiotherapy groups [ 11 , 25 ]. Bladder recurrence is common postoperatively in patients with UTUC and a risk factor for a poor prognosis [ 26 ]. The bladder recurrence rate can reach 27 to 47% [ 27 , 28 ] after surgery, as described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Another study found that a distal ureteral tumor was an independent risk factor for the development of MIBC and radical cystectomy. (7) In 1974, Grabstald described the first case of tumor surrounding the ileal stoma 4 years after a radical cystectomy, assigning the direct implantation of tumor cells during surgery as the probable cause. It was treated with surgical resection, and before performing the urinary diversion, the skin was thoroughly washed and the instruments were replaced.…”
Section: Discussionmentioning
confidence: 99%